The challenges of socio-economic reintegration of maoist ex-combatants in Nepal : a gender view - Sthapit, Lorina; Resurreccion, Bernadette P.; Doneys, Philippe; Grunbuhel, Clemens; Her Majesty the Queen{u2019}s Scholarship for the Asian Environment Development Program, Government of Thailand (Pathum Thani, Thailand : Asian Institute of Technology, 2013)
The unique feature of Nepal{u2019}s 10 yeararmed conflict was the participation of women as Maoist guerilla fighters who fought alongside men for equality. However, the post-conflict reintegration process led by the government and the UN did not take into account the gendered socio-economic conditions of the male and female Maoist ex-combatants. Therefore, the focus of this research is the challenges of the male and female Maoist ex-combatants in the post-conflict Nepal from a gender viewpoint. The findings of this research claimthe existence ofgender-specific stigmasof male and female ex-combatants including the double stigma of the female ex-combatants.Similarly,the findingsimply that because of lack of skill, education, assets and social capital, the ex-combatants are facing livelihood difficulties such as unemployment. Femaleex-combatants were seen as being particularly vulnerable because of the persisting patriarchal society in Nepalthat restricts women{u2019}s choices, mobility and opportunities.The findings also show that male and female ex-combatants displayed gender-specific responses to these challenge in lack of options andlimited external support. On the positive side,however,the results revealed the constructive actions of the ex-combatants in response to the lack of adequate and effective external support: female respondents{u2019} initiative to learn marketable skills and to gain education degrees and the collective initiative ofmale respondents to bring an agriculture and economic {u2018}revolution.The inferences drawn form this study indicate that stigmas and livelihood difficulties are inversely associated with reintegration.In addition, gender-specific stigmas and livelihood related struggles areinterlocked with social structures that determine gender roles and norms. The research argues that thesocio-economic challengesthat the male and female Maoist ex-combatants are facing and their responsestowards the challengesare theresult of thereintegration of the ex-combatants into thepre-existing gender-biased social order and the inability of the {u2018}revolution{u2019} to change the existing socio-economic structures plaguing Nepal. Moreover, evidences showthatthe Nepali Disarmament, Demobilization, Rehabilitation and Reintegration (DDRR) not only failed to recognize gender-specific challenges, but also reinforced the existing socio-economic challenges the ex-combatants faced.
A thesis submitted in partial fulfillment of the requirements for the Degreeof Master of Science in Gender and Development Studies, School of Environment, Resources and Development
Thesis (M. Sc.) - Asian Institute of Technology, 2013
Keywords: Women in war -- Nepal